The Price and Welfare Effects of The Value-Added Tax : Evidence from Mexico - Mariscal, Rodrigo (IMF Working Papers; Working Paper ;, 2018)
In this paper we analyze the incidence of the VAT and its effects on the income distribution. To identify these effects, we rely on two tax reforms undertaken in Mexico that increased the VAT rate for a group of cities and left the rest unaffected. We compare the inflation rate of the affected cities with the exempted cities before and after the law changed. We find that the effect on prices is limited and conclude that the burden of the tax is indeed shared between producers and consumers. Regarding welfare, we find that the VAT is progressive in both absolute and relative terms to the overall expenditure. Finally, we show that an identical change in the VAT rate when inflation is high and persistent doubles its pass-through to inflation and its welfare loss for the average household.